FIGURATIVE LANGUAGE IN TAYLOR SWIFT’S SONG ALBUM OF RED - Ngera, Thresia Gloria Embu; Weda, Sukardi; Nur, Riola Haya (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research aims to determine the types of figurative language that appeared in